PENGARUH LITERASI KEUANGAN DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PENGGUNAAN SHOPEE PAYLATER MELALUI FINANCIAL TECHNOLOGY PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS ABDURACHMAN SALEH SITUBONDO - Hidayanti, Nor; Wiryaningtyas, Dwi Perwitasari; Ariyantiningsih, Febri; Ciptasari, Ayu Dita Windra (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The aim of this research is to determine the effect of Financial Literacy and Perceived Risk on the Decision to Use ShopeePaylaterthrough Financial Technology in Abdurachman Saleh Situbondo Faculty of Economics and Business Students. The sampling technique used in this research is Purposive Sampling. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that financial literacy has a positive and significant effect on Financial Technology, Perceived risk has a positive and significant effect on Financial Technology, Financial Literacy has a positive and significant effect on the decision to use, Perceived risk has a positive but not significant effect on the decision to use, Financial Technology has a positive and significant effect on the decision to use. Financial literacy has a positive and significant effect on the decision to use through Financial Technology. Perceived risk has a positive but not significant effect on the decision to use through Financial Technology.